Less may be more for stage I epithelial Wilms tumors. Issue 12 (8th April 2020) - Gessler, Manfred; Graf, Norbert
Abstract : A retrospective analysis of the Children's Oncology Group AREN03B2 study has revealed that stage I epithelial‐predominant favorable‐histology Wilms tumors have excellent outcomes, and this suggests that primary treatment with surgery alone should be investigated in future protocols.